Biomass, nutrient accumulation, and weed suppression by mix of cover crops. - SILVA, M. A. (2023)
Cover crops, isolated or mixed, provide several benefits to agricultural systems, such as nutrient cycling and weed control. The present study aimed to determine the biomass production and nutrient accumulation of a cover crop mix and its effects on weed suppression (biomass production), in the off-season, in a no-tillage area in the Cerrado region. The experimental design was in randomized blocks with six treatments and eight replications. Treatments comprised five cover crop mixes plus the control treatment (fallow). Mixes of cover crops, cultivated between grain harvests in a no-tillage system in the Cerrado region, efficiently reduced weed shoot biomass in the three evaluation periods, 30, 70, and 210 days after sowing. Additionally, it is concluded that the mixes 5 (Black oats, Buckwheat, Millet, Piatã grass, and Crotalaria ochroleuca) and 4 (C. spectabilis, Buckwheat, Pearl millet, and Crotalaria breviflora) are the best among those evaluated for Cerrado conditions because they produce more biomass in the offseason, due to the greater availability of nutrients to the soil, in addition to providing less biomass of weeds compared to fallow.